Repositioning a country for global manufacturing competitiveness: a case of South Africa. Issue 2 (13th January 2020) - Gates, Gareth Earle; Adetunji, Olufemi
Abstract : Purpose: This study aims to develop an artifact to measure the level of manufacturing competitiveness of a country in the global context and provide a suitable interpretation mechanism for the measured values, and to provide prescriptive solution where necessary so that the country can develop an actionable plan of program to move from the current level of global competitiveness to another such that they could provide more economic opportunities for their citizenry. Design/methodology/approach: A manufacturing competitive index (MCI) was developed which includes relevant variables to capture a country's manufacturing activity level in an economy with a balanced perspective. Reliable international sources were used. Ward algorithm was used to identify clear clusters of performance upon which competitive gaps were measured and improvement projects were identified and prioritized to obtain the best value for cluster transitional plan. Findings: This study shows that the case country is not doing as well as it wants to believe, even when the relevant technology import measures were included in the expanded metric, but also, the next level of competitiveness is achievable within the national budget if proper prioritization is done. Originality/value: The paper presents a cocktail of indexes that is more exhaustive of MCI, including both research capacity and technology import variables. It also uses clustering mechanism to provide a proper context to interpret the MCI scores in the context of peer nations. It presents a gap determination methodology and shows how priority projects could be logically selected to close measured gaps based on anticipated value from budget expenses